The Prevalence of Familial Hyperaldosteronism in Apparently Sporadic Primary Aldosteronism in Germany: a Single Center Experience - Pallauf, A.; Schirpenbach, C.; Zwermann, O.; Fischer, E.; Morak, M.; Holinski-Feder, E.; Hofbauer, L.; Beuschlein, F.; Reincke, M. (Hormone and Metabolic Research, 2012)
Primary aldosteronism (PA) is the most frequent cause of secondary arterial hypertension. To date 3 forms of familial hyperaldosteronism (FH) have been described accounting for a small percentage of all PA cases. In Germany, the prevalence of FH is currently unknown. Our aim was to determine the prevalence of familiarity in a large cohort of patients with PA. A total of 166 patients with apparently sporadic PA in Munich were investigated. FH types I, II, and III were identified using established clinical, biochemical, and molecular criteria. Among the 166 patients with PA, 2 patients (1.2%) reported a family history suggestive of FH. None of the 166 patients showed clinical, endocrine, or genetic evidence of FH type I. The 2 families had characteristic features of FH type II. Family A had 3 subjects affected out of 11 evaluated family members. Family B had 3 out of 4. Bilateral adrenal hyperplasia and unilateral adrenal adenoma were found within the same family. FH type I and FH type III are rare in Germany. With a prevalence of 1.2%, FH type II seems to be more common in apparently sporadic PA than had been assumed so far.
Keywords: conn syndrome; primary aldosteronism; genetics; CYP11B1/CYP11B2